Promoção de comportamentos sociais em criança com TEA: intervenção mediada por pares e histórias sociais - Zampieri, Jessica (Universidade Federal de São Carlos, 2026)
The school constitutes a fundamental space for the integral development, learning, and social interaction of individuals. However, despite advances in Inclusive Education policies, the Brazilian educational system still faces challenges in ensuring the effective inclusion of students who are the target population of Special Education. Among this group, students with Autism Spectrum Disorder (ASD) stand out, as their characteristics—such as deficits in communication and social interaction, as well as restricted and repetitive patterns of behavior—may result in barriers to participation and socialization within the school context. In this scenario, the present study aimed to investigate the effects of a peer-mediated intervention program associated with the use of social stories to promote social behaviors in a child with ASD in Early Childhood Education. The research was conducted using a single-subject experimental design, with pre-test and post-test, involving a class from the final year of Early Childhood Education, with the effects specifically analyzed in one target participant diagnosed with ASD level 1 support needs. The dependent variables included observable social behaviors, such as parallel and shared play, initiating and responding to conversational attempts, and positive and negative social interactions. The results indicated a reduction in parallel play and an increase in shared play, an expansion of the communicative repertoire, and an increase in positive interactions, along with a decrease in negative interactions, as well as evidence of generalization of the intervention effects. It is concluded that the peer mediated intervention associated with the use of social stories proved to be promising for promoting social behaviors in Early Childhood Education, pointing to directions for future research and inclusive practices, including the expansion of the program to other levels of Early Childhood Education, the implementation of strategies by education professionals and family members, as well as further exploration of the use of social stories.
Promotion of social behaviors in a child with ASD: peer-mediated intervention and social stories
Keywords: Educação especial; Special education; Intervenção mediada por pares; Peer-mediated intervention; Transtorno do espectro autista; Autism spectrum disorder; Generalização; Generalization; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::PROGRAMACAO DE CONDICOES DE ENSINO; 4. Educação de Qualidade